Stereotactic Radiosurgery With Versus Without Embolization for Brain Arteriovenous Malformations. Issue 2 (5th October 2020) - Chen, Ching-Jen; Ding, Dale; Lee, Cheng-Chia; Kearns, Kathryn N; Pomeraniec, I Jonathan; Cifarelli, Christopher P; Arsanious, David E; Liscak, Roman; Hanuska, Jaromir; Williams, Brian J; Yusuf, Mehran B; Woo, Shiao Y; et al.
Abstract: BACKGROUND: Prior comparisons of brain arteriovenous malformations (AVMs) treated using stereotactic radiosurgery (SRS) with or without embolization were inherently flawed, due to differences in the pretreatment nidus volumes. OBJECTIVE: To compare the outcomes of embolization and SRS, vs SRS alone for AVMs using pre-embolization malformation features. METHODS: We retrospectively reviewed International Radiosurgery Research Foundation AVM databases from 1987 to 2018. Patients were categorized into the embolization and SRS (E + SRS) or SRS alone (SRS-only) cohorts. The 2 cohorts were matched in a 1:1 ratio using propensity scores. Primary outcome was defined as AVM obliteration. Secondary outcomes were post-SRS hemorrhage, all-cause mortality, radiologic and symptomatic radiation-induced changes (RIC), and cyst formation. RESULTS: The matched cohorts each comprised 101 patients. Crude AVM obliteration rates were similar between the matched E + SRS vs SRS-only cohorts (48.5% vs 54.5%; odds ratio = 0.788, P  = .399). Cumulative probabilities of obliteration at 3, 4, 5, and 6 yr were also similar between the E + SRS (33.0%, 46.4%, 56.2%, and 60.8%, respectively) and SRS-only (32.9%, 46.2%, 56.0%, and 60.6%, respectively) cohorts (subhazard ratio (SHR) = 1.005, P  = .981). Cumulative probabilities of radiologic RIC at 3, 4, 5, and 6 yr were lower in the E + SRS (25.0%, 25.7%, 26.7%, and 26.7%, respectively) vs SRS-only (45.3%, 46.2%, 47.8%, and 47.8%, respectively) cohort (SHR = 0.478, P  = .004). Symptomatic and asymptomatic embolization-related complication rates were 8.3% and 18.6%, respectively. Rates of post-SRS hemorrhage, all-cause mortality, symptomatic RIC, and cyst formation were similar between the matched cohorts. CONCLUSION: This study refutes the prevalent notion that AVM embolization negatively affects the likelihood of obliteration after SRS. Graphical Abstract: